Analisis Kepuasan Kerja Perawat Terhadap Manajemen Keperawatan Di RSUD Waluyo Jati Kraksaan: Analysis of Nurse Job Satisfaction with Nursing Management At RSUD Waluyo Jati Kraksaan - Titik Titik Suhartini (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2020)
Hospital is one form of health service that provides services in full in accordance with theneeds of the community. The most dominant health personnel providing services are nursing staff, so that nurses in particular are one of the determinants of achieving quality hospital services. Nurses in carrying out their duties can be influenced by many things, especially the acceptance of nurses in carrying out their work, in this case the performance of nurses is one of the determinants of job satisfaction felt by nurses. Nurse job satisfaction will affect the management process carried out in the hospital, especially in each inpatient room. The purpose of this study was to analyze nurse satisfaction with nursing management at RSUD Waluyo Jati Kraksaan.In this study using a correlational analytic research design. The population is inpatientnurses at RSUD Waluyo Jati Kraksaan. The sampling technique used is stratified randomsampling. Data analysis using Kendall's Tau test to determine the relationship of variableswith a significance level of p ? 0.05.The results of the study showed that nurses' job satisfaction was mostly satisfied, as many as 73 respondents (81.5%) while overall nursing management was in a good category. Theresults of the test data analysis obtained P = 0,000 with ? = 0.05 so that the conclusion there is a relationship between nurse job satisfaction and nursing management.Management of nursing management, especially in the inpatient room, is influenced by nurse job satisfaction. All forms of management management methods carried out are strongly influenced by the work ability of each nurse so that all forms of nursing activity programs will provide good results for nursing services